Interleukin-10 resolves pain hypersensitivity induced by cisplatin by reversing sensory neuron hyperexcitability. Issue 10 (October 2020) - Laumet, Geoffroy; Bavencoffe, Alexis; Edralin, Jules D.; Huo, Xiao-Jiao; Walters, Edgar T.; Dantzer, Robert; Heijnen, Cobi J.; Kavelaars, Annemieke
Abstract : Abstract: Understanding the mechanisms that drive transition from acute to chronic pain is essential to identify new therapeutic targets. The importance of endogenous resolution pathways acting as a "brake" to prevent development of chronic pain has been largely ignored. We examined the role of interleukin-10 (IL-10) in resolution of neuropathic pain induced by cisplatin. In search of an underlying mechanism, we studied the effect of cisplatin and IL-10 on spontaneous activity (SA) in dorsal root ganglia neurons. Cisplatin (2 mg/kg daily for 3 days) induced mechanical hypersensitivity that resolved within 3 weeks. In both sexes, resolution of mechanical hypersensitivity was delayed in Il10 −/− mice, in WT mice treated intrathecally with neutralizing anti-IL-10 antibody, and in mice with cell-targeted deletion of IL-10R1 on advillin-positive sensory neurons. Electrophysiologically, small- to medium-sized dorsal root ganglia neurons from cisplatin-treated mice displayed an increase in the incidence of SA. Cisplatin treatment also depolarized the resting membrane potential, and decreased action potential voltage threshold and rheobase, while increasing ongoing activity at −45 mV and the amplitude of depolarizing spontaneous fluctuations. In vitro addition of IL-10 (10 ng/mL) reversed the effect of cisplatin on SA and on the depolarizing spontaneous fluctuation amplitudes, but unexpectedly had little effect on the other electrophysiological parameters affected by cisplatin. Collectively, our findings challenge the prevailing concept that IL-10 resolves pain solely by dampening neuroinflammation and demonstrate in a model of chemotherapy-induced neuropathic pain that endogenous IL-10 prevents transition to chronic pain by binding to IL-10 receptors on sensory neurons to regulate their activity. Abstract : Supplemental Digital Content is Available in the Text.Resolution of pain depends on endogenous IL-10 signaling; IL-10 binds to its receptor on sensory neurons to reverse cisplatin-induced neuronal hyperactivity and pain hypersensitivity.